RADIO NAVIGATION SYSTEM BROADBAND SIGNAL SEARCH - Aleksey S. Marugin; Vladimir K. Orlov; Rumiya R. Khaziakhmetova (Известия высших учебных заведений России: Радиоэлектроника, 2018)
The study object is the search procedure for a ground-based radionavigation system signal using noise-like discrete signals with a long baseline. A comparative analysis of the signal search quality indicators is carried out, which is the most time-consuming procedure with different navigation signal modulation formats in the worst-case conditions and with a limited frequency resource allocated to the system. Bandwidth efficiency of noise-like signals (NLS) with phase shift keying (PSK) and minimal frequency shift keying (MFSK) are analyzed. Relations are obtained for the average maximum search time of the navigation signal with a fixed probability of correct search completion. The qualitative indicators of the search procedure for PSK and MFSK are compared for the same band pass effectiveness and elementary symbol duration. The analysis results show that under the conditions of equal restrictions on the occupied frequency range and the same requirements for the search procedure reliability, NLS MFSK search is effective and implementable at much lower time costs than NLS with traditional binary PSK.